RT 027 Community Participation in Waste Management in Puspita Bengkuring Housing Environment, Samarinda City - Ahmad Yani; Rusli; Trisna Waty Riza Eryani; Kiki Risky Tania (PT FORMOSA CENDEKIA GLOBAL, 2023)
Research on Community Participation of RT 027 Residents in Waste Management in the Puspita Bengkuring Housing Environment, Samarinda City, along with the level of community participation in managing waste The research method used is a qualitative descriptive approach, using interactive model data analysis from Miles, Huberman, and Saldana (2014). The results of the research show that residents of Rukun Tetangga 027 actively participate directly in thoughts, labor, goods and money. The level of community participation in terms of waste management is still not optimal, so it is necessary to increase participation, especially in terms of participation in separating waste based on its type, participating in waste management fees so that waste management can be properly organized, increasing community participation in community service implementation, and realizing the program as soon as possible, so that a high level of participation can be achieved.